Manufacturing of Soil Coefficient Permeability Meter with Data Acquisition System Based on Internet of Things (IoT) - Fahrur Aslami; Elysa Nensy Irawan; Melania Suweni Muntini; Dwa Desa Warnana; Ahmad Syahdi Al Khawarizmi (Jurnal Fisika dan Aplikasinya, 2023)
Soil permeability coefficient and measuring instrument using a data acquisition system based on Internet of Things (IoT) has been successfully made. The measuring equipment uses the falling head permeameter concept. MPX10GP sensor is used to measure water level. The measurement range is 6-40 cm water level, to obtain + 36 permeability coefficient value of each 1 cm. The data from the subsequent measurement systems is transmitted into the internet network so that it can be accessed by smartphone. Based on the measurement results of three samples, the slopes of Mount Ngantang have a soil permeability coefficient value of 0.0016 cm/s, the Institut Teknologi Sepuluh Nopember (ITS) pond embankment is 0.0005 cm/s, and the Bengawan Solo River embankment is 0.0002 cm/s. These results match with the reference and the difference value is only 2.7%. By using this research method, it is expected to draw up a map of the area that is prone to landslides quickly and accurately.